(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Assessment of the prevalence of congenital heart defects per pregnant women for pregnancy examination and management at the prenatal and neonatal diagnostic screening center in 2021. Subjects-methods: From 1/2021 to 12/2021, 2159 pregnant women came to fetal morphological ultrasound at the prenatal and neonatal screening center of Nghe An Children’s Hospital, a retrospective cross-sectional descriptive research method. Results: There were 760 cases of fetal morphological abnormalities, accounting for 35.2%. In 760 abnormal cases, there were 198 cases of cardiac malformation monitoring, accounting for 26%, 61 cases out of 198 cases were diagnosed with BTBS, accounting for 2.8%, Rate of BTBS in children who came to ultrasound examination. Postnatal check up is 17%. Conclusions: Examination of cardiac abnormalities on ultrasound from 18 weeks to 28 weeks gestation is very valuable in the attitude of treatment for patients.